Conceptualising the role of values in environmental governance and management: an analytical framework - Christopher Kuster; Michelle Voyer; Catherine Moyle; Anna Lewis (Ecosystems and People)
Human and ecological values influence all aspects of governance and management processes and in doing so, contribute to environmental decisions and outcomes. However, there is an absence of coherent and well-developed guidance to assist understanding of how values influence the different aspects of environmental governance and management. This paper addresses the gap between environmental values theory and governance and management practice. With in the context of Government policy making and implementation we examine the meaning and influence of principle, contextual and relational values in connection to the normative, empirical, and applied aspects of environmental governance and management. We present a conceptual framework articulating the relationships between value types and their influence on governance and management processes, demonstrating that management actions (applied) are based on empirical understandings (contextual values) through a lens of normative judgments (principle values). In addition to clarifying the role of values in governance and management, the framework is envisaged as an analytical tool to assist management practitioners to: 1) elucidate the values operating in a given governance or management setting; 2) tease out how different values influence the aspects of governance and management (e.g. goal setting, assessment, and choosing and applying management strategies), and how those aspects interact to influence outcomes; and 3) to identify potential value conflicts or synergies to guide the integration of multiple environmental interests, priorities and knowledges.